Hagar and Ishmael: A Commentary - Cohen, Aryeh (Interpretation, 2014)
This essay offers a commentary on the short story of Hagar and Ishmael’s expulsion at the hands of Abraham (Gen 21:14–20). The commentary lays a claim on traditional interpretation but is not itself necessarily a traditional interpretation.